Penguatan Literasi Budaya Berbasis Digital melalui EthnoGring sebagai Strategi Pendokumentasian, Konservasi, dan Promosi Desa Wisata Budaya Nyanggring yang Berkelanjutan - Deby Febriyan Eprilianto; Danang Wijoyanto; I Gde Agung Sri Sidhimantra; Mohamad Hermy Hibatulloh; Lisa Amelia Sari (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program focuses on enhancing digital literacy, documenting cultural traditions, and developing integrated promotional media through the EthnoGring platform in Tlemang Cultural Tourism Village, Lamongan. The activities were conducted in collaboration with the local tourism group, Pokdarwis “Bukit Inggil,” through stages of needs assessment, digital literacy training, cultural content production and curation, platform development, and monitoring and evaluation. The results indicate that digitalization strengthens community capacity to manage tourism promotion while simultaneously safeguarding cultural heritage in the face of modernization. Cultural outputs such as documentaries, photographs of traditional rituals, interview transcripts with cultural figures, and an e-book on the Nyanggring tradition serve not only as promotional tools but also as efforts to conserve collective community knowledge. The integration of these outputs into the EthnoGring platform, equipped with public service and tourism information features, highlights the strategic role of digital innovation in supporting sustainable tourism village development. Early impacts include broader exposure of Tlemang’s cultural heritage, the emergence of local economic initiatives, and the establishment of a more adaptive community organization. Although challenges remain, particularly in digital infrastructure, collective engagement and institutional support serve as key foundations for sustainability. Therefore, EthnoGring contributes not only to cultural preservation but also to strengthening the social, economic, and institutional dimensions of sustainable tourism.